HB-HTA focus in a tertiary hospitals' network in Northern Italy: A three-years experience analysis - Sharma, Sudwaric; Castaldi, Silvana; Perrone, Pier Mario; Cusmai, Michele Giovanni (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Nowadays Health Technology Assessment (HTA) is becoming more important in the hospital management, until the conception of Hospital Based HTA (HB-HTA), considered as a tool of HTA that is a multidisciplinary process to determine the value of a health technology in health sector. The aims of this study are the investigation of the current state of the art and of the diffusion of the HTA culture in hospitals (HB-HTA) also the analysis of the thinking of healthcare professionals regarding the usefulness of HTA.Methods: The study was performed through the administration of two questionnaires respectively to hospitals’ HealthCare Workers (HCW) to assess the HTA’s knowledge and to hospitals’ HCW that have submitted a new technologies or devices’ request to Direction between 2017 and 2019.Results: Considering 988 questionnaires send to HCW only 416 (42.1%) answer were collected, with a higher attention towards HTA made by physicians (148; 35,6%). It’s fundamental to observe that despite a mean response rate all the population shows interest for the HB-HTA concept as an instrument to help the hospital management. About the 23 questionnaires to HCW that have made request show a higher attention and knowledge to HTA.Conclusions: In conclusion, in the current welfare landscape and for the future developments that will ensue from it, especially in the Italian context due to the increase of healthcare funds provided by the NRRP (National Recovery and Resilience Plan), the adoption of the HB-HTA method will represent a strategic lever to support clinical and organizational decision-making processes governance.